Facile approach to synthesis the curly leaf-like Nano-sheets of g-C3N4 with enhanced photocatalytic ability. (9th March 2018) - Zhao, Zhiren; Li, Kebin; Muhmood, Tahir; Xia, Mingzhu; Wang, Fengyun
Abstract: Exfoliation of porous g-C3 N4 has been proved a very effective way to prepare g-C3 N4 nanosheets (2D layered materials). Here, we present an environment-friendly, high-efficiency and easy scale-up preparation method of curly leaf-like g-C3 N4 nanosheets (CL-CN) by liquid-phase exfoliation of honeycomb-like porous g-C3 N4 (HP-CN). Two-dimensional curly nanosheets have induced excellent physicochemical properties, i.e. large surface area, high fluorescence quantum efficiency, wide band gap and good water-dispersibility. The photocatalytic performance of CL-CN in degradation of RhB under visible light is much better than that of honeycomb-like porous g-C3 N4 and bulk g-C3 N4 . The improved photocatalytic performance of CL-CN is well explained by the improved physicochemical properties and photocatalytic mechanism. In addition, CL-CN being a 2D layered material with excellent photoluminescence characteristic and non-toxic behavior can be widely applied in bio-medicine, bio-imaging and biosensors field.